2004
DOI: 10.1159/000077393
|View full text |Cite
|
Sign up to set email alerts
|

Sono-Guided Endometrial Biopsy: Comparison with Hysteroscopy Biopsy

Abstract: Objective: To assess the feasibility, tolerance and diagnostic accuracy of endometrial biopsy (EB) during sonohysterography (SH) compared to EB after hysteroscopy (HSC) in endometrial disorders. Methods: 105 consecutive patients with irregular uterine bleeding were included prospectively in the calendar year 2001. SH and flexible HSC were performed in an office setting, subsequently and in a random order, by two different practitioners blind to the former experiment. SH-EB was performed using a 3.1-mm ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…The feasibility of diagnostic hysteroscopy in women at risk of HNPCC was similar to that in the overall population in an earlier study [9]. Furthermore, the 11% failure rate was consistent with our experience in the general population of women with abnormal vaginal bleeding [14]. In an earlier study, we found no significant safety differences between flexible hysteroscopy and sonohysterography [14].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The feasibility of diagnostic hysteroscopy in women at risk of HNPCC was similar to that in the overall population in an earlier study [9]. Furthermore, the 11% failure rate was consistent with our experience in the general population of women with abnormal vaginal bleeding [14]. In an earlier study, we found no significant safety differences between flexible hysteroscopy and sonohysterography [14].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the 11% failure rate was consistent with our experience in the general population of women with abnormal vaginal bleeding [14]. In an earlier study, we found no significant safety differences between flexible hysteroscopy and sonohysterography [14]. However, the limited number of patients who underwent follow-up hysteroscopies at the recommended time interval (1 year) in the present study leaves some uncertainty regarding safety.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Poorer SIS sensitivity and specificity have been reported [9,18,19]. In the group of 105 patients sonohysteroscopy failed to detect endometrial polyps in 30 cases [18], SIS may also lead to erroneous diagnosis of blood clots as endometrial polyps [20].…”
Section: Discussionmentioning
confidence: 99%
“…Poorer SIS sensitivity and specificity have been reported [9,18,19]. In the group of 105 patients sonohysteroscopy failed to detect endometrial polyps in 30 cases [18], SIS may also lead to erroneous diagnosis of blood clots as endometrial polyps [20]. Many authors do not regard sonohysterography results as sufficient evidence to confirm or exclude endometrial abnormalities [4,6,12,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%